Light exposure leads to reorganization of microglomeruli in the mushroom bodies and influences juvenile hormone levels in the honeybee. Issue 11 (10th June 2014) - Scholl, Christina; Wang, Ying; Krischke, Markus; Mueller, Martin J.; Amdam, Gro V.; Rössler, Wolfgang
ABSTRACT Honeybees show a remarkable behavioral plasticity at the transition from nursing inside the hive to foraging for nectar and/or pollen outside. This plasticity is important for age‐related division of labor in honeybee colonies. The behavioral transition is associated with significant volume and synaptic changes in the mushroom bodies (MBs), brain centers for sensory integration, learning, and memory. We tested whether precocious sensory exposure to light leads to changes in the density of synaptic complexes [microglomeruli (MG)] in the MBs. The results show that exposure to light pulses over 3 days induces a significant decrease in the MG density in visual subregions (collar) of the MB. Earlier studies had shown that foragers have increased levels of juvenile hormone (JH) co‐occurring with a decrease of vitellogenin (Vg). Previous work further established that RNAi‐mediated knockdown of vg and ultraspiracle (usp) induced an upregulation of JH levels, which can lead to precocious foraging. By disturbing both Vg and JH pathways using gene knockdown of vg and usp, we tested whether the changes in the hormonal system directly affect MG densities. Our study shows that MG numbers remained unchanged when Vg and JH pathways were perturbed, suggesting no direct hormonal influences on MG densities. However, mass spectrometry detection of JH revealed that precocious light exposure triggered an increase in JH levels in the hemolymph (HL) of young bees. This suggests a dual effect following light exposure via direct effects on MG reorganization in the MB calyx and a possible positive feedback on HL JH levels. © 2014 Wiley Periodicals, Inc. Develop Neurobiol 74: 1141–1153, 2014